Priming effect increases with depth in a boreal forest soil. (August 2016) - Karhu, Kristiina; Hilasvuori, Emmi; Fritze, Hannu; Biasi, Christina; Nykänen, Hannu; Liski, Jari; Vanhala, Pekka; Heinonsalo, Jussi; Pumpanen, Jukka
Abstract: Climate warming increases labile carbon (C) inputs to soil through increased photosynthesis and C allocation belowground. This could counterintuitively lead to losses of soil C via priming effects (PE): the stimulation of soil organic matter (SOM) decomposition caused by labile C addition. Systematic quantification of PEs in different ecosystems is needed. We measured PEs of free-living soil microbes in different layers of a boreal forest soil, and found that the relative magnitude of the PE increased with soil depth. The relationship between relative PE and the added glucose amount also depended on the soil layer. Our results indicate that the decomposition of SOM in deeper soil layers could be significantly increased due to PE, if labile C inputs into these layers increase. Highlights: We studied priming effects (PE) in different layers of a boreal forest soil. 13 C labeled glucose was added at different amounts relative to microbial biomass. PE increased with depth, and thus with decreasing C and N availability. The relationship between PE and the added glucose amount depended on the soil layer. If C inputs into subsoil increase, SOM decomposition could be enhanced through PEs.